Phylogenetic Relationships in Orobanchaceae Inferred From Low-Copy Nuclear Genes: Consolidation of Major Clades and Identification of a Novel Position of the Non-photosynthetic Orobanche Clade Sister to All Other Parasitic Orobanchaceae - Li, Xi; Feng, Tao; Randle, Chris; Schneeweiss, Gerald M. (Frontiers in Plant Science, 2019)
Molecular phylogenetic analyses have greatly advanced our understanding of phylogenetic relationships in Orobanchaceae, a model system to study parasitism in angiosperms. As members of this group may lack some genes widely used for phylogenetic analysis and exhibit varying degrees of accelerated base substitution in other genes, relationships among major clades identified previously remain contentious. To improve inferences of phylogenetic relationships in Orobanchaceae, we used two pentatricopeptide repeat (PPR) and three low-copy nuclear (LCN) genes, two of which have been developed for this study. Resolving power and level of support strongly differed among markers. Despite considerable incongruence among newly and previously sequenced markers, monophyly of major clades identified in previous studies was confirmed and, especially in analyses of concatenated data, strongly supported after the exclusion of a small group of East Asian genera (Pterygiella and Phtheirospermum) from the Euphrasia-Rhinanthus clade. The position of the Orobanche clade sister to all other parasitic Orobanchaceae may indicate that the shift to holoparasitism occurred early in the evolution of the family. Although well supported in analyses of concatenated data comprising ten loci (five newly and five previously sequenced), relationships among major clades, most prominently the Striga-Alectra clade, the Euphrasia-Rhinanthus clade, and the Castilleja-Pedicularis clade, were uncertain because of strongly supported incongruence also among well-resolving loci. Despite the limitations of using a few selected loci, congruence among markers with respect to circumscription of major clades of Orobanchaceae renders those frameworks for detailed, species-level, phylogenetic studies.